2021
DOI: 10.3389/fimmu.2021.577766
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib Exerts In Vitro Immunomodulatory Activity on Sarcomas via Dendritic Cells and Synergizes With PD-1 Blockade

Abstract: BackgroundHigh-grade sarcomas are a heterogeneous group of aggressive tumors arising in bone and soft tissues. After relapse, treatment options are limited. The multi-targeted receptor tyrosine kinase inhibitors (TKIs) sunitinib and inhibitor of PD-1 (anti-PD-1) nivolumab have shown antitumor activity in selected subtypes. In this study, we examine the role of TKIs and PD-1 based therapy in in vitro cocultures of sarcoma.MethodsThe human osteosarcoma (SaOS-2) and synovial sarcoma (SYO-1) cell lines were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In vitro, similar effects have been observed in STS: sunitinib prompted PDL-1 upregulation, dendritic cell maturation and T-cell activation. Furthermore, upregulation of T-reg cells was abrogated [54]. Thus, combination of anti-PD and TKIs may mitigate the VEGF-driven immunosuppressive state of STS.…”
Section: Discussionmentioning
confidence: 97%
“…In vitro, similar effects have been observed in STS: sunitinib prompted PDL-1 upregulation, dendritic cell maturation and T-cell activation. Furthermore, upregulation of T-reg cells was abrogated [54]. Thus, combination of anti-PD and TKIs may mitigate the VEGF-driven immunosuppressive state of STS.…”
Section: Discussionmentioning
confidence: 97%
“…Dasatinib is an antagonist of the SRC family of kinases, and may potentially induce T-cell response leading to improved survival of malignant pleural mesothelioma ( Chen et al, 2020 ). Chelerythrine, Tamoxifen, Tanespimycin and Sunitinib have also been shown to have anticancer effects in a variety of cancers ( Heng and Cheah, 2020 ; Wang and Liu, 2020 ; Ocadlikova et al, 2021 ; Su et al, 2021 ). These evidences also indicate the prospect of targeting these two lncRNAs for the treatment of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Zheng et al found that the hyperactive STAT3 triggered PD‐L1 expression, while STAT3‐specific inhibitor suppressed PD‐L1, leading to the growth reduction of osteosarcoma cells 28 . Darina et al reported that vascular endothelial growth factor and platelet‐derived growth factor‐specific inhibitor sunitinib synergized with PD‐L1 antibody nivolumab, interrupting osteosarcoma progression 29 . Liu et al revealed that miR‐200a rescued PD‐L1 expression from PTEN, enhancing osteosarcoma malignancies 13 .…”
Section: Discussionmentioning
confidence: 99%